A study of pregnancy after endometrial ablation using linked population data. (12th October 2020) - Ibiebele, Ibinabo; Nippita, Tanya A.; Baber, Rodney; Torvaldsen, Siranda
Abstract: Introduction: Endometrial ablation encapsulates a range of procedures undertaken to destroy the endometrial lining of the uterus as a treatment for heavy menstrual bleeding in women who no longer wish to bear children. Pregnancy following ablation, while unlikely, can occur and may carry higher rates of complications. The aim of this study was to identify factors associated with post‐endometrial ablation pregnancy and to describe pregnancy and birth outcomes for post‐endometrial ablation pregnancies. Material and methods: This population‐based data linkage study included all female residents of New South Wales, Australia, aged 15‐50 years with a hospital admission between July 2001 to June 2014 who birthed between July 2001 and June 2015. Cox proportional hazard regression was used to estimate associations between women's characteristics and post‐endometrial ablation pregnancy of at least 20 weeks' gestation. Descriptive statistics were used to characterize pregnancy and birth outcomes. Results: Of 18 559 women with an endometrial ablation, 575 (3.1%) had a post‐ablation pregnancy of at least 20 weeks' gestation. Nulliparity (adjusted hazard ratio [aHR] 12.2, 95% confidence interval [CI] 9.1‐16.2), older age (35‐39 years: aHR 0.39, 95% CI 0.29‐0.51; 40‐44 years: aHR 0.06, 95% CI 0.04‐0.11), marital status (single: aHR 0.67, 95% CI 0.55‐0.83; widowed/divorced/separated: aHR 0.58, 95% CI 0.36‐0.94) and a diagnosis of heavy menstrual bleeding (aHR 0.09, 95% CI 0.07‐0.13) were associated with post‐ablation pregnancy. There were high rates of cesarean delivery (43%), preterm birth (13%), twin or higher order pregnancies (9%) and stillbirth (13.3/1000 births) among these post‐ablation pregnancies. Conclusions: Nulliparity at the time of endometrial ablation is associated with increased risk of post‐ablation pregnancy, highlighting the importance of careful discussion and consideration of treatment options for heavy menstrual bleeding.